Islandinium pacificum sp. nov., a new dinoflagellate cyst from the upper Quaternary of the northeast Pacific. (2nd January 2020) - Gurdebeke, Pieter R.; Mertens, Kenneth Neil; Pospelova, Vera; Van Nieuwenhove, Nicolas; Louwye, Stephen
Abstract: Round brown process-bearing cysts (RBPC) produced by dinoflagellates (Dinophyceae) occur as an important part of assemblage diversities in seafloor sediments worldwide. Here a new species, Islandinium pacificum, is described from surface sediment samples from coastal waters of British Columbia (Canada). Additional observations are made on material from the Holocene of Kyuquot Sound (Vancouver Island, Canada) and the Eemian of the Vøring Plateau (North Atlantic). The cysts have a smooth wall and bear acuminate processes with barbs. Incubation experiments reveal an affinity with the motile stage Protoperidinium mutsuense . The ecology of the new species is specified.